Multiplicity and complexity: a qualitative exploration of influences on prescribing in UK general practice - Carter, Mary (BMJ Open, 2021)
OBJECTIVES: Despite widespread availability of evidence-based guidelines to inform rational use of medicines, considerable unwarranted variation exists in prescribing. A greater understanding of key determinants of contemporary prescribing in UK general practice could inform strategies to promote evidence-based prescribing. This study explored (1) current influences on prescribing in general practice and (2) the possibility that general practice-based pharmacists (PBPs) may contribute to greater engagement with evidence-based prescribing. DESIGN: Semistructured, telephone interviews and a focus group were conducted, audio-recorded and transcribed verbatim. Thematic analysis was undertaken. PARTICIPANTS: General practice prescribers: general practitioners (GPs), PBPs, nurses. Key informants: individuals within the National Health Service (NHS) with responsibility for influencing, monitoring and measuring general practice prescribing. SETTING: General practices and NHS organisations in England. RESULTS: Interviews with 17 prescribers (GPs (n=6), PBPs (n=6), nurses (n=5)) and 6 key informants, and one focus group with five key informants were undertaken between November 2018 and April 2019. Determinants operating at individual, practice and societal levels impacted prescribing and guideline use. Prescribers’ professional backgrounds, for example, nursing, pharmacy, patient populations and patient pressure were perceived as substantial influences, as well as media portrayal and public perceptions of medicines. Prescribers identified practice-level determinants of prescribing, including practice culture and shared beliefs. Key informants tended to emphasise higher-level influences, including NHS policies, availability of support and advice from secondary care and generic challenges associated with medicines use, for example, multimorbidity. Participants expressed mixed views about the potential of PBPs to promote evidence-based prescribing in general practice. CONCLUSION: Prescribing in UK general practice is influenced by multiple intersecting factors. Strategies to promote evidence-based prescribing should target modifiable influences at practice and individual levels. Customising strategies for medical and non-medical prescribers may maximise their effectiveness.